Feminine Writing Style in the Works of Kurdish and persian Women Story Writers - Ranjdar Azad Azeez; Hemdad Hussin Bakir (Zanco Journal of Human Sciences, 2026)
This study titled ‘Feminine Writing Style in the Works of Kurdish Women Story Writers’ aims at identifying writing styles in the works written by Kurdish and Persian women story writers. Feminine stories as an independent literary genre have their own distinctive frame and features, and narrated in a particular feminine style. Some of these features distinguish feminine from masculine works. They resort to use certain words, expressions and statements reflect their own distinctive views, perspectives and environment, such as words and rephrase related to housekeeping, makeup, domestic stuffs, maternity, etc. Women are known for their accuracy; therefore, they dive into the details while describing or illustrating an issue, making use of descriptive words. In terms of syntactic structure, they usually utilize simple and short constructions. Feminine works are full of hesitant and doubt tools. Their discourses are full of expressions that are related to emotion, curses, prayers and non-linguistic symbols. To illustrate these differences from Sara Mills perspective, the stories of Kurdish and Persian women writers have been analyzed comparatively at three linguistic levels-the word, the sentence, and the discourse - in order to demonstrate how the feminine writing style is practiced across these layers.